A qualitative descriptive study examining the impact of child‐raising experience on Japanese family doctors - Manabu Fujihara; Satoko Watanabe; Kuniko Kodama; Koki Nakamura; Maham Stanyon; Satoshi Kanke; Ryuki Kassai (Journal of General and Family Medicine)
Abstract Background The Patient‐Centered Clinical Method (PCCM) plays an important role in family doctors' ability to communicate effectively with patients. Although the parenting experiences of healthcare providers can be utilized to communicate with patients, it is unclear how they contribute to family doctors' practice. Methods A qualitative descriptive study focusing on the parenting experiences of Japanese family doctors and their perceptions of how these experiences interfaced with their clinical practice of the PCCM was conducted. Participants were selected using snowball sampling, and the data were collected via semi‐structured interviews while recording online, which were transcribed verbatim and analyzed using qualitative descriptive analysis, with data‐derived codes being systematically applied and reflexively interpreted. The categories were refined concurrently with the interviews. Once it was established that no additional categories were required, the recruitment and analysis process was concluded. Results The eight participants were recruited, and the following themes were extracted; these were “Developing patience and new perspectives through raising children,” “Empathizing with the experiences of others,” “Building awareness of social factors and home context,” “Reflecting on one's own words and behavior,” “Forming partnerships with patients through shared parenting experiences,” and “Facilitating interpersonal growth.” Conclusion The communication skills that have been refined through personal experiences of raising children are transferable between professional and family situations. This research shows that such skills are not mutually exclusive to professional or family settings and can be used effectively to improve clinical practice as part of the PCCM model of consulting.